A comparative analysis in UK mortgage banking sector in the perspective of risk assessment after sub-prime crisis - Jang, Jr Lung (2008)
As a result of the worldwide liquidity crunch caused by sub-prime mortgage crisis, the provision of a broad analysis of UK mortgage banking sector in the perspective of risk assessment is attempted for investors to make future investment decision and for depositors and regulators to identify potential risks in banks. The main purpose of this study is to explore whether the potential risks in UK mortgage banks can be detected before sub-prime crisis occurs. Northern Rock, HBOS and Alliance & Leicester are thus selected as research subjects, and the reason why Northern Rock suffered a more serious liquidity problem than the other two is also focused. This study primarily involves a comparison of financial position and exposure to different risks of three mortgage banks via annual reports and historical stock prices. In this context, the analysis of annual reports, historical simulation approach of Value at Risk and stress test are thus implemented. After a series of meticulous examination, this research reflects the weak financial position of Northern Rock in terms of capital adequacy, asset quality, profitability, liquidity risk and market risk. This may imply that the potential risks in UK mortgage banks such as Northern Rock could be detected before sub-prime mortgage crisis occurs.